Role of the Immune System in the Development of the Central Nervous System - Morimoto, Keiko; Nakajima, Kazunori (Frontiers in Neuroscience, 2019)
The central nervous system (CNS) and the immune system are both intricate and highly organized systems that regulate the entire body, with both sharing certain common features in developmental mechanisms and operational modes. It is known that innate immunity-related molecules, such as cytokines, toll-like receptors, the complement family, and acquired immunity-related molecules, such as the major histocompatibility complex and antibody receptors, are also expressed in the brain and play important roles in brain development. Moreover, although the brain has previously been regarded as an immune-privileged site, it is known to contain lymphatic vessels. Not only microglia but also lymphocytes regulate cognition and play a vital role in the formation of neuronal circuits. This review provides an overview of the function of immune cells and immune molecules in the CNS, with particular emphasis on their effect on neural developmental processes.